PENGARUH UMUR PERUSAHAAN, FINANCIAL DISTRESS, GENDER KOMITE AUDIT TERHADAP KETEPATAN WAKTU PENYAMPAIAN PELAPORAN KEUANGAN DAN OPINI AUDIT SEBAGAI PEMODERASI - Meyvi Devtari Bella; Harry Budiantoro (Jurnal Akuntansi, 2023)
This study aims to determine the effect of company age, financial distress, gender of the audit committee on the timeliness of financial reporting submission with audit opinion as moderation and its review from an Islamic point of view. The population in this study were manufacturing companies listed on the IDX for the 2017-2021 period, totalling 152 companies. The sampling technique used purposive sampling. The total sample used was 43 companies. The data in this study used secondary data. The analysis method used is the multiple linear analysis method and moderated linear regression analysis (MRA) which is processed with the SPSS 29 application. The partial results showed that company age and audit committee gender had no effect on the timeliness of financial reporting submission, financial distress had a positive effect on the timeliness of financial reporting submission. Simultaneously, company age, financial distress, audit committee gender have a significant effect on the timeliness of financial reporting submission. The results of the MRA test conducted show that audit opinion is unable to moderate the effect of company age and audit committee gender on the timeliness of financial reporting submission. Meanwhile, financial distress is able to moderate audit opinion on the timeliness of financial reporting submission.